Critical success factors of total quality management in autonomous driving business models. Issue 1 (1st January 2020) - Wang, Zinan; Meckl, Reinhard
Abstract: Autonomous driving is undoubtedly one of the most strategically relevant and financially promising developing industries. The requirements for autonomous driving systems' reliability are dramatically higher than in the driver-based car industry. This study explores a model to identify the structure and evaluate the critical success factors (CSFs) of total quality management (TQM) in the autonomous driving industry. Fifteen CSFs are defined according to the expected ecosystem of autonomous driving. VDA and IATF 16, 949 quality systems are used as starting points for deriving the CSFs for an autonomous driving TQM system (AD-TQM). The CSFs are integrated into a framework to reveal their effects and interdependencies. The framework is qualitatively empirically tested and designed to be employed as a model for future (quantitative empirical) research.